Financial burden faced by breastfeeding mothers caring for children diagnosed with cancer in Ghana; an exploratory qualitative study - Margaret Marfo; Angela Kwartemaa Acheampong; Comfort Asare (BMC, 2024)
Abstract Background When children are diagnosed of cancer, parents face varied financial issues. Among some of the identifiable factors that cause financial challenges among breastfeeding mothers include the high cost of childhood cancer care. The high cost of childhood cancer care could impede the sustainability of access to prompt care. There is paucity of literature on the financial burdens faced by breastfeeding mothers with children diagnosed with cancer in Ghana. Therefore, this study sought to explore the financial burden faced by mothers with breastfeeding children diagnosed with cancer. Methods The study employed qualitative exploratory descriptive design. One-on-one interviews were conducted among 13 mothers with breastfeeding children diagnosed of cancer. Permission was sought for data to be recorded, transcribed concurrently and inductive content analysis done. Results Three main themes emerged after data analysis: High cost (sub-themes; expensive medications, laboratory investigation fees, and cost of mothers' feeding), Public support (sub-themes; appeal for funds, national health insurance scheme) and Self-financing (loans, personal savings). Most of the breastfeeding mothers narrated that high cost of childhood cancer care generated financial distress to them. They shared that the cost involved in purchasing their children's cancer medications, paying for laboratory investigations and feeding themselves to produce adequate breastmilk to feed their children were challenging. Some of the mothers self-financed the cost of their children's cancer care through loans and personal savings. Conclusion Government and other stakeholders should allocate annual budget and funds towards childhood cancer care to lessen the financial burden breastfeeding mothers caring for children with cancer experience.